Fisheries bycatch and conservation priorities of young sharks (Chondrichthyes: Elasmobranchii) in the Eastern Mediterranean. Issue 2 (3rd April 2022) - Erguden, Deniz; Kabasakal, Hakan; Ayas, Deniz
Abstract : Sharks are one of the most threatened groups of marine animals because of high exploitation rates coupled with low resilience to fishing pressure. We provide information on the current status of the young sharks caught in fishing nets in Iskenderun and Mersin Bays in the eastern Mediterranean, based on fishery-dependent surveys conducted between 2010 and 2021. Sharks were found in bycatches in trawling nets, trammel nets, bottom longlines and fishing lines. Incidental captures of young-of-the-year or juvenile specimens (n=269) included 15 species and the data indicate that İskenderun and Mersin Bays may serve as a nursery ground for the new-born and young individuals especially for the Blackmouth Catshark ( Galeus melastomus ), the Lesser Spotted Dogfish ( Scyliorhinus canicula ), and the Velvet Belly ( Etmopterus spinax ). If necessary measures are taken, bycatch can be reduced to a certain limit, or even eliminated for shark species in the Mediterranean Sea.